PENGARUH PERSEPSI STANDAR AUDIT, POTENSI DIRI, MOTIVASI EKONOMI, DAN MOTIVASI KARIR TERHADAP PROFESI AUDITOR EKSTERNAL (STUDI PADA MAHASISWA JURUSAN AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA BANDA ACEH) - Auni, Dara; Yahya, M. Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This studyaims to examine the influence of perception, potension, economic motivation and career motivation. The samples of this research are student accounting program of Syiah Kuala University and resulted 74 kuesioner. The Samplesare collected using simple random sampling method. Data were collected from student accounting program branch of 2012 and 2013, then data analyzed by multiple regression analysis. The results of this research show that (1) perception, potension, economic motivation and career motivation have influence for , external auditor profession.(2) perception influence for external auditor profession, (3) potension influence for external auditor profession, and (4) economic motivation influence for external auditor profession, (5) career motivation influence for external auditor profession.